Activity of (1-benzyl-4-triazolyl)-indole-2-carboxamides against Toxoplasma gondii and Cryptosporidium parvum. (August 2022) - Khan, Shahbaz M.; Garcia Hernandez, Anolan; Allaie, Idrees Mehraj; Grooms, Gregory M.; Li, Kun; Witola, William H.; Stec, Jozef
Abstract: Parasitic diseases such as toxoplasmosis and cryptosporidiosis remain serious global health challenges, not only to humans but also to domestic animals and wildlife. With only limited treatment options available, Toxoplasma gondii and Cryptosporidium parvum (the causative agents of toxoplasmosis and cryptosporidiosis, respectively) constitute a substantial health threat especially to young children and immunocompromised individuals. Herein, we report the synthesis and biological evaluation of a series of novel (1-benzyl-4-triazolyl)-indole-2-carboxamides and related compounds that show efficacy against T. gondii and C. parvum . Closely related analogs 7c (JS-2-30) and 7e (JS-2-44) showed low micromolar activity with IC50 indices ranging between 2.95 μM and 7.63 μM against both T. gondii and C. parvum, whereas the compound representing (1-adamantyl)-4-phenyl-triazole, 11b (JS-2-41), showed very good activity with an IC50 of 1.94 μM, and good selectivity against T. gondii in vitro . Importantly, compounds JS-2-41 and JS-2-44 showed appreciable in vivo efficacy in decreasing the number of T. gondii cysts in the brains of Brown Norway rats . Together, these results indicate that (1-benzyl-4-triazolyl)-indole-2-carboxamides and (1-adamantyl)-4-phenyl-triazoles are potential hits for medicinal chemistry explorations in search for novel antiparasitic agents for effective treatment of cryptosporidiosis and toxoplasmosis. Graphical abstract: Image 1 Highlights: (1-Benzyl-4-triazolyl)-indole-2-carboxamide show interesting antiparasitic activity. Compounds' concentrations of 1.94–7.63 μM inhibited growth of T. gondii & C. parvum . The best hits displayed in vivo efficacy comparable to the standard drug atovaquone. Those compounds show good potential for further development as antiparasitic agents.